Dasar-Dasar untuk Melakukan Editing Digital: Karakter Video Digital, Resolusi, Pixel Depth, Frame Rate, dan Aspek Rasio - Winda Kustiawan; Nia Handayani; Melinda Rianto Putri; M. Fatur Rizki Ramadhan; Khairil Anzar; Rio Irawan Munthe (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study aims to examine the fundamental concepts of digital editing by analyzing the main characteristics of digital video, including resolution, pixel depth, frame rate, and aspect ratio. The research employs a library research method with a qualitative descriptive approach through the review of scientific journals, books, and relevant academic publications. The results indicate that resolution affects image sharpness and detail, pixel depth determines color quality and gradation, frame rate influences motion smoothness, and aspect ratio affects the visual composition and compatibility of video content across different platforms. These four components are interconnected and play a crucial role in producing high-quality digital videos. Understanding these characteristics enables editors and content creators to make appropriate technical decisions during production and post-production processes. Therefore, mastery of digital video characteristics is an essential foundation for creating effective, efficient, and high-quality audiovisual content in the digital era.